Eksistensi Majelis Ta`lim Asyifah di Kecamatan Pattallassang Kabupaten Takalar - Hidayah Quraisy; Jamaluddin Arifin (Universitas Muhammadiyah Makassar, 2017)
Majelis Ta'lim is a non-formal Islamic educational institution that can give a considerable contribution in the formation of morals and personal Muslims in accordance with the guidance of Rasulullah SAW. This study aims to determine the factors causing no successor Assembly Ta'lim Asyifah In Pattalassang District Takalar regency, to know the process of the successor of Majelis Ta'lim Asyifah In Pattallassang District Takalar District. The type of research used is descriptive qualitative research method by way of determining the sample through Purposive Sampling technique by selecting some informants who have criteria that have been determined by the researcher who knows about the Assembly Ta'lim Assyifah. This research is supported by data collection is done by observation, interview, documentation of the photo. The results showed that in general the factors causing the absence of the successor of Majelis Ta'lim Asyifah were the lack of socialization about the activities of Majelis Ta'lim, the absence of other people's interest in joining Majelis Ta'lim Asyifah, the absence of spare time to follow the activities of Majelis Ta'lim Asyiah. The process of the creation of the successor of Majelis Ta'lim Asyifah is to increase the socialization of the existence of Majelis Ta'lim's activities.Keywords: Majelis Ta'lim, Socialization, Society